2006
DOI: 10.1542/peds.2005-1832
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic Complications of Overweight in Children and Adolescents

Abstract: OBJECTIVE-Few studies have quantified the prevalence of weight-related orthopedic conditions in otherwise healthy overweight children. The goal of the present investigation was to describe the musculoskeletal consequences of pediatric overweight in a large pediatric cohort of children that included severely overweight children.METHODS-Medical charts from 227 overweight and 128 nonoverweight children and adolescents who were enrolled in pediatric clinical studies at the National Institutes of Health from 1996 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
288
2
36

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(344 citation statements)
references
References 28 publications
18
288
2
36
Order By: Relevance
“…Landin [21], in fact, demonstrated that between the ages of 10 and 15 years, the incidence of sports-related injuries doubles in girls and more than triples in boys. At the same time, multiple articles have demonstrated that obese children participate in sports much less and have substantially more difficulty with physical activities than their nonobese counterparts [3,13,33,36]. Thus, the effective exposure of obese adolescents to one of the most common causes of injuries-sports, and especially competitive sports-is much lower, thus possibly lowering their risk of fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Landin [21], in fact, demonstrated that between the ages of 10 and 15 years, the incidence of sports-related injuries doubles in girls and more than triples in boys. At the same time, multiple articles have demonstrated that obese children participate in sports much less and have substantially more difficulty with physical activities than their nonobese counterparts [3,13,33,36]. Thus, the effective exposure of obese adolescents to one of the most common causes of injuries-sports, and especially competitive sports-is much lower, thus possibly lowering their risk of fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal comorbidities have become a recent focus of research in obese children. Obese children report more frequent and severe joint pain [13,51,53] and lower extremity malalignment is more prevalent in overweight and obese children [28][29][30]52]. Like with obese adults, obese children report lower function and healthrelated quality of life compared with their healthy peers [38,41,53,63], but less is known about factors in obese children that may contribute to poor function and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Overweight and obese children have a higher prevalence of musculoskeletal pain [13,53], particularly in the lower extremity (LE) [13,51,53]. A cross-sectional study in 2459 children showed that overweight and obese children more frequently report LE pain and problems and more frequently visit their family physician for pain and problems in the LE compared with healthy-weight children [22].…”
Section: Introductionmentioning
confidence: 99%
“…A crosssectional survey of 9 to 17 year old children based on self-report showed an association between obesity and the occurrence of injuries, 9 and a chart review of the records of children and adolescents found an association between overweight orthopedic difficulties, including musculoskeletal discomfort and impaired mobility. 10 The combination of increased body mass and previous ankle sprain is associated with a higher risk of subsequent sprains in high school athletes. 11 Both adults and children who sustain an ankle injury and are obese are likely to have greater long-term ankle morbidity than their normal weight counterparts.…”
Section: Introductionmentioning
confidence: 99%